Analisis Pelaksanaan Online System Pajak Daerah Dalam Rangka Penerimaan Pajak Hiburan dan Pajak Restoran pada Suku Badan Pajak dan Retribusi Daerah Kota Administrasi Jakart Pusat Tahun 2014- 2016 - Sulistiyowati .; Nurina Sabila (Jurnal Ekonomi, 2018)
This study aims to analyze the Implementation of the Online Regional Tax System in the Context of Receiving Entertainment Taxes and Restaurant Taxes at the Regional Tax and Levies Agency for Central Jakarta City Administration in 2014-2016. This study uses a descriptive type of research with a qualitative approach. The data used in this study are primary data and secondary data. Data collection techniques used are literature study, observation, interviews and documentation. The results of the study conclude that (1) The implementation of Entertainment Tax and Restaurant Tax receipts received through the Regional Tax Online System, namely where Taxpayers can pay their tax bills through BRI CMS, which is provided by BRI Bank. (2) The highest percentage of Entertainment Tax revenue effectiveness was achieved in 2016 at 63.35% and the lowest percentage occurred in 2015 at 35.84%. The highest percentage of restaurant tax revenue effectiveness occurred in 2014 at 109.35% and the lowest percentage occurred in 2015 at 92.63%. (3) The obstacles faced in implementing the receipt of Entertainment Tax and Restaurant Tax are the lack of Compliance Level of Taxpayers with their Tax Collections and the presence of Taxpayers who still do not understand the Regional Tax Online System.